(untitled) (Journal of Nepal Geological Society, 2023)
Exploration of copper ore in the Nepal Himalayas has been carried out by different researchers at different times. The author conducted detailed geological studies and mineral exploration in some of the copper and polymetallic prospects and also reviewed the literature related to copper prospects in Nepal. The present research is able to delineate two distinct copper ore mineralization belts extending from west to east and identify the promising sites for copper ore and polymetallic mineralization that could be feasible for mining. The northern mineralization belt lies close to the Main Central Thrust where the mineralization occurs mostly in metamorphic rocks of garnet amphibolite facies in Darchula, Bajhang, Gorkha, Dolakha, Solukhumbu and Ilam districts. The southern mineralization belt in the Lesser Himalaya occurs in low-grade metamorphic rocks of greenschist facies in Dadeldhura, Rukum, Baglung, Myagdi, Tanahun, Dhadhing, Makwanpur, Dolakha, Udaypur, Bhojpur and Ilam districts. Most of these prospects were locally exploited on a small scale by traditional mining before 1951. Almost all mineralization in both belts is related to hydrothermal dissemination, irregular multiple vein type, replacement and cavity fillings and only a few polymetallic mineralizations at the exo-contact zone of granite bodies. The ore minerals were concentrated during the processes of regional metamorphism at the time of Himalayan upheaval. In general, the copper content in the northern belt appears to be higher in grade and tonnage as compared to the southern belt. The frequent association of tungsten, molybdenum, bismuth, nickel, tin, lead, zinc ores and traces of gold suggests the urgent need for further detailed exploration and evaluation of selected prospects which could be economic deposits and feasible for mining.